2015
DOI: 10.1111/1471-0307.12209
|View full text |Cite
|
Sign up to set email alerts
|

Milk oligosaccharides: A review

Abstract: Milk oligosaccharides (OSs) confer unique health benefits to the neonate. Although human digestive enzymes cannot degrade these sugars, they support specific commensal microbes and act as decoys to prevent the adhesion of pathogenic micro-organisms to gastrointestinal cells. The limited availability of human milk oligosaccharides (HMOs) impedes research into these molecules and their potential applications in functional food formulations. Recent studies show that complex OSs with fucose and N-acetyl neuraminic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 166 publications
3
39
0
3
Order By: Relevance
“…However, in OPO-A group, no more carbon sources could be consumed by fecal microbiota other than OPO. It was consistent with the previous article that lactose supports the growth of intestinal microbes (Oliveira et al, 2015). Thus, lactose was used by fecal microbiota, and it produced large amounts of Lactic acid resulting in a sharp decrease in pH in the OPO-P group.…”
Section: Discussionsupporting
confidence: 92%
“…However, in OPO-A group, no more carbon sources could be consumed by fecal microbiota other than OPO. It was consistent with the previous article that lactose supports the growth of intestinal microbes (Oliveira et al, 2015). Thus, lactose was used by fecal microbiota, and it produced large amounts of Lactic acid resulting in a sharp decrease in pH in the OPO-P group.…”
Section: Discussionsupporting
confidence: 92%
“…The milk fat globule membrane (MFGM) in raw bovine milk contains components (lipids, proteins, and carbohydrates) that are believed to interact with the gut microbiome of the growing infant (Bourlieu et al, 2017). In addition, bovine milk contains various kinds of oligosaccharides that can also promote the establishment of a healthy gut microbiome (Oliveira, Wilbey, Grandison, & Roseiro, 2015;Robinson, 2019). As a result, these milk constituents may provide protection against inflammatory diseases and contribute to the development of a healthy immune system.…”
Section: Gastrointestinal Fatementioning
confidence: 99%
“…Animal milk also contains oligosaccharides with similar structure and function as human milk oligosaccharides that can be a functional food ingredient [45]. Sialyllactose is N-acetylneuraminic acid (sialic acid) bound to β-lactose, and Luo et al [46] showed that high permeation of 3′-sialyllactose is obtained by using an integrated UF/NF membrane system for the valorization of dairy by-products with engineered sialidase.…”
Section: Milk Concentration and Component Separationmentioning
confidence: 99%